Rotavirus meningitis in an adult with transient aphasia. (October 2022) - Collercandy, Nived; Migueres, Marion; Hallak, Benjamin; Garnier, Camille; Rousset, Stella; Delourme, Adrien; Delobel, Pierre; Martin-Blondel, Guillaume
Highlights: We consider Rotavirus in the differential diagnosis of aseptic meningitis with gastroenteritis. XXX. XXX. Abstract: We identified an additional case of documented Rotavirus meningitis in an adult with full medical history. A previously healthy 37-year-old patient presented herself for transient aphasia associated with fever and headaches at the end of a one-week history of gastroenteritis. Cerebrospinal fluid (CSF) analysis revealed lymphocytic meningitis, and treatment with aciclovir was initiated. Rotavirus A reverse transcription-polymerase chain reaction (RT-PCR) was positive in CSF and the patient's stools in favor of Rotavirus meningitis. Testing for other viruses was negative. Magnetic resonance imaging (MRI) showed no signs of encephalitis. Aphasia was resolutive in less than 12 hours, and no neurological symptoms relapsed. All symptoms evolved favorably despite aciclovir discontinuation. Viral sequencing methods have recently identified unexpected viruses as potential causative agents in meningitis, including Rotavirus. We confirm the detectability of Rotavirus in the analysis of CSF in the context of Rotavirus gastroenteritis in an adult. This case suggests postviral headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL) syndrome may be linked to previously undetected direct viral infection of the central nervous system. Therefore, clinicians should consider Rotavirus meningitis in diagnosing meningitis associated with gastroenteritis in adults.